Peran Pemerintah dalam Pengembangan Ekonomi Hinterland di Kabupaten Rokan Hulu Melalui Pemanfaatan Sumber Daya Alam Sawit - Ahmad Khusaini; Lutfia Bamatraf; Belia Afifah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
This study aims to analyze the role of government in the development of the hinterlandeconomy in Rokan Hulu Regency through the utilization of natural resources, focusing ona case study of oil palm plantations in accelerating regional economic growth. The methodused in this study is a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats)to evaluate the strengths, weaknesses, opportunities, and threats associated with thedevelopment of the oil palm plantation sector in the district. This study uses a qualitativeapproach by collecting data through literature studies, interviews with relevantstakeholders, and analysis of existing policies. The data collected will be analyzeddescriptively and interpreted to gain a deep understanding of the role of government in thedevelopment of the hinterland economy in Rokan Hulu Regency. From the results of thestudy using SWOT analysis of the role of government in developing the hinterland economyin Rokan Hulu Regency through natural resources (oil palm industry) are the strengths andweaknesses of internal factors of 1.82 and external factors of 0.27. In this effort, thereneeds to be implementation of appropriate policies between all related parties so as to help achieve sustainable economic growth, create jobs, improve community welfare, andmaintain environmental sustainability in Rokan Hulu Regency.